Divisão de tarefas em colônias de Dinoponera quadriceps (Hymenoptera, Formicidae, Ponerinae) - Medeiros, Ingrid Araújo de (2016)
In social insects, the division of labor is a hallmark, being considered the key for the ecological success of them. This process raises an important question: how can ant workers, with their simple cognitive system, coordinate efficiently the tasks performed by other workers or even by different group of workers. Aiming to clarify this question, we observed the task allocation in colonies of Dinoponera quadriceps. The study was carried out in the Behavioral Biology Lab, at UFRN. In all observations and experiments, workers were individually marked with an alphanumeric tag glued in the thorax. We used instantaneous focal method to observe the colonies, registering activities of each worker every 15 minutes. In the first part of the study we investigate the effect of age on the division of labor. We observed four colonies during eight months. Each colony was observed two hours a day, three times a week. We found that young individuals perform more nest work, and also have as the main task the immature care. Thus, D. quadriceps serves a temporal polyethism flexible model. In the second part of the study, we investigated whether the workers have behavioral flexibility, being capable of responding efficiently to a disturbance. To answer this question, it was used three colonies in two different conditions: (1) foragers were removed and (2) nurse were removed. Each condition last for nine days, and colonies were observed two hours during these nine days. As a result, colonies were capable of allocating nestmates to the task that demanded more workers due to the removal, either foraging or nursing. In the third and last part of the study, we tested the effect of the workers’ weight on the task allocation. During five consecutive months four colonies were observed once a month for one hour. The next day after the observation, we removed all workers and weighted them. Our data suggest that workers that perform nest work are heavier than foragers and individuals that forage and do nest work. Our data suggest that the body weight of individuals remain engaged in activities internal to the nest is larger, they are heavier compared to those individuals that carry out these tasks and intermediate are heavier than foragers. Thus, body weight and age are modulators of task allocation in D. quadriceps, and flexibility in these colonies make them able to distribute their activities according to the demand of the colony.